2012
DOI: 10.1002/lt.23488
|View full text |Cite
|
Sign up to set email alerts
|

Mini-incision right hepatic lobectomy with or without laparoscopic assistance for living donor hepatectomy

Abstract: Minimally invasive procedures are considered to be safe and effective approaches to the management of surgical liver disease. However, this indication remains controversial for living donor hepatectomy. Between 2000 and 2011, living donor right hepatectomy (LDRH) was performed 58 times. Standard right hepatectomy was performed in 30 patients via a subcostal incision with a midline extension. Minimally invasive procedures began to be used for LDRH in 2008. A hybrid technique (hand-assisted laparoscopic liver mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(86 citation statements)
references
References 35 publications
6
80
0
Order By: Relevance
“…Although current evidence does not indicate which of these approaches is best, HALS and hybrid method are claimed by their proponents to be beneficial for large lesions,9, 56 posterior lesions57, 58 and donor hepatectomy 59, 60, 61, 62, 63, 64. HALS and the hybrid method can be used to manage intraoperative difficulties and can theoretically decrease the frequency of conversion to full open incision.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Although current evidence does not indicate which of these approaches is best, HALS and hybrid method are claimed by their proponents to be beneficial for large lesions,9, 56 posterior lesions57, 58 and donor hepatectomy 59, 60, 61, 62, 63, 64. HALS and the hybrid method can be used to manage intraoperative difficulties and can theoretically decrease the frequency of conversion to full open incision.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Some authors reported the feasibility of major hepatectomy under midline incision including living donor hepatectomy (18,19). Lee et al concluded that the procedure after an upper midline incision is more difficult in male donors with large fatty livers and deep truncal cavities.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically in patients with low BMI (< 25 or less) and small anterior/posterior diameter, certain surgeons have described an upper midline approach through which they are able to accomplish complete mobilization of the right lobe from its retroperitoneal attachments and off the right side of the vena cava [22]. They then proceed with hilar dissection and transection of the liver using a hanging maneuver similar to what is described in the laparoscopically assisted approach.…”
Section: Technique For Ladrhmentioning
confidence: 99%
“…-laparoscopic left lateral segmentectomy [1,2] -laparoscopic hand-assisted right hepatectomy [13,16] -laparoscopic hand-assisted right hepatectomy using midline incision "Hybrid Method" [17,18,19•] -laparoscopic hand-assisted right hepatectomy using a transverse or subcostal incision [13,20] -single port laparoscopic-assisted right hepatectomy using a right subcostal incision [20] -right hepatectomy through upper midline laparotomy [11,21] -right hepatectomy through an upper midline minilaparotomy with or without laparoscopic assistance [22] -totally laparoscopic full left hepatectomy [23•] -pure laparoscopic right hepatectomy [3] -robot-assisted right hepatectomy [24•] In this chapter, we will describe the advantages and disadvantages of some of the important variations of these minimally invasive approaches to donor hepatectomy. Table 1 provides a descriptive overview and comparison of these approaches.…”
Section: Introductionmentioning
confidence: 99%